Immunosuppressive properties of Wharton's jelly derived mesenchymal stromal cells in the treatment of graft versus host disease in rat model - Lopez Rodriguez, Yelica Virginia (Kansas State University, 2013)
Graft Versus Host Disease (GVHD) is the major complication following hematopoietic stem cell transplantation. GVHD is activated by immunocompetent T cells presented in the donor grafted tissue. Due to the increased use of bone marrow transplantation to treat diverse malignancies, the incidence of GVHD has shown a notable increase. Depending of the degree of immunological mismatch between donor and host, 50-70% of patients develop GVHD after allogeneic Bone Marrow Transplantation (BMT). Once GVHD develops, mortality reaches up to 50% in humans. Several studies using Mesenchymal Stromal Cells (MSCs) to prevent and treat GVHD have produced controversial results. It is thought that distinct MSCs sources used in those studies might be an important factor that produces different outcomes. For cellular therapy, the most attractive characteristics of MSCs are their reduced immunogenic potential, and their abilities to modulate immune responses. This dissertation addressed the hypothesis that Wharton’s jelly cells (WJCs) would prevent the pathology and death associated with GVHD after BMT. To accomplish this, I created a clinically relevant model of GVHD by transplanting allogeneic bone marrow across minor histocompatibility antigen (HA) barriers in the rat. To enhance alloreactive T-cell stimulation, bone marrow (BM) was co-administered with a fraction of CD8[superscript]+ cells magnetically selected from spleen to induce GVHD. Bone marrow tissue was isolated from a donor rat Fischer 344 (F344, RT1lv) and transplanted into lethally irradiated (10 Gray) Lewis rat (LEW, RT1l). Once GVHD was induced, MSCs derived from umbilical cord WJCs were either co-transplanted at day 0 with bone marrow, or given on day 2 post-BMT intravenously. The prophylactic potential of WJCs in an in vivo GVHD model was assessed as survival time, clinical symptomatology occurrence, and histopathology injuries in target tissues. Results indicate that while co-administration of WJCs with hematopoietic cells on day 0 failed to alleviate GVHD associated symptomatology and mortality. WJCs administered on day 2 post-induction ameliorated GVHD-associated symptomatology, improved engraftment and survival.
Keywords: Graft versus host disease; Umbilical cord mesenchymal stromal cells; Wharton's jelly cells; GVHD rat model; Veterinary Medicine (0778)